Diagnostic of Higher Education in Guinea : Current Outcomes and Challenges - World Bank Group (World Bank, Washington, DC, 2017)
The World Bank’s Country Partnership Strategy (CPS) for Guinea in FY 2014-17 confirmed the Government’s priority to build 21st century skills for improved employability and to implement systemic reforms. Guinea is emerging from years of political and economic isolation and instability. The democratic election of President Alpha Condé has opened the door for the international donor community, including the World Bank, to come forward and support the new government. Its important reform agenda, PREMA, has helped restore the confidence of the international community. The World Bank will partner with the Government of Guinea to develop systems that will ‘improve lagging human development indicators for absolute poverty reduction, through more efficient and transparent allocation of resources, and to build shared prosperity by aligning the business environment and education system with Guinea’s economy’ (World Bank, 2013, pp. 1). This is in line with the government’s priorities, as per the Third National Poverty Reduction Strategy Paper (PRSP3) approved in 2013. The PRSP3 aims to reduce poverty and to create and sustain a vibrant private economy by maximizing rents from Guinea’s substantial mining sector. The Bank supports the Government’s agenda on improving human capital by: (a) promoting both the quantity and quality of education and (b) upgrading skills for the needs of emerging and export-oriented sectors such as agriculture, tourism, mining, and telecommunications and Information and Communications Technology (ICT). In 2012, the Government requested special support from the Bank in the form of technical assistance to conduct an analysis of the higher education system. This analysis will be used to prepare a comprehensive higher education strategy to meet the needs of both the economy and the labor market. Since the early 2000s, the Bank had limited involvement in this critical sub-sector. Per the Government’s request, the Bank mobilized resources to engage in policy and analytical work in the areas of governance, financing, and diagnostic of skills demand and supply from a new employer survey prepared specifically under this technical assistance project.